Use the properties of operations and rules for multiplying and dividing to solve:

(−3/5)×(5/16)×(7/12)÷(−3/16)×(−5/7)
please show me how you got the answer

3 answers

To solve this expression, we can simplify step by step using the properties of operations and rules for multiplying and dividing fractions.

First, let's start by canceling out the common factors in the numerator and denominator:

(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)
= (-3/5) × (1/16) × (7/12) ÷ (1/16) × (5/7)
= (-3/5) × (7/12) ÷ (5/7)

Next, we can simplify the multiplication and division:

= (-3/5) × (7/12) ÷ (5/7)
= (-3/5) × (7/12) × (7/5)
= (-3 × 7) / (5 × 12) × (7/5)
= -21/60 × 7/5

Now, we can simplify the expression further by canceling out common factors:

= -21/60 × 7/5
= -7/20 × 7/5
= (-7 × 7)/(20 × 5)
= -49/100

Therefore, the final answer is -49/100.
wrong
Apologies for the mistake. Let's do the calculations again:

(-3/5) × (5/16) × (7/12) ÷ (-3/16) × (-5/7)

First, we simplify the numerator and denominator:

Numerator:
(-3/5) × (5/16) × (7/12) = (-3 × 5 × 7) / (5 × 16 × 12) = -105/960

Denominator:
(-3/16) × (-5/7) = (3 × 5) / (16 × 7) = 15/112

Now, we can divide the numerator by the denominator:

(-105/960) ÷ (15/112)

When dividing fractions, we can multiply the first fraction by the reciprocal of the second fraction:

(-105/960) × (112/15) = (-105 × 112) / (960 × 15) = -11760/14400

Next, we can simplify the fraction by dividing both the numerator and denominator by their greatest common divisor (which is 240):

(-11760/14400) ÷ 240/240 = (-49/60) ÷ 1 = -49/60

Therefore, the final answer is -49/60.